2021
DOI: 10.3390/nano11112901
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Silver Nanoparticles: What We Know and What Do We Need to Know?

Abstract: Nanobiotechnology is considered to be one of the fastest emerging fields. It is still a relatively new and exciting area of research with considerable potential for development. Among the inorganic nanomaterials, biogenically synthesized silver nanoparticles (bio-AgNPs) have been frequently used due to their unique physicochemical properties that result not only from their shape and size but also from surface coatings of natural origin. These properties determine antibacterial, antifungal, antiprotozoal, antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 247 publications
(319 reference statements)
2
29
0
4
Order By: Relevance
“…In addition, the increase in cell density enhances the effect of quorum sensing, causing genetic mutations that reduce the metabolic activity; in other words, a combative environment increases the phenotypic variation between bacteria, thereby providing favorable defense and progress, ultimately leading to antibiotic resistance [ 32 , 33 ]. Biofilm formation on the surfaces of medical devices is therefore a key feature of disease progression, and so the antiadhesion and antibacterial functionalization of PVC-ETTs with hydrophilic polymers and stable broad-spectrum antibacterial agents is particularly important in the prevention of biofilm formation and bacterial infection [ 34 37 ]. It is therefore also critical to suppress bacterial adhesion and multiplication during the initial stage.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the increase in cell density enhances the effect of quorum sensing, causing genetic mutations that reduce the metabolic activity; in other words, a combative environment increases the phenotypic variation between bacteria, thereby providing favorable defense and progress, ultimately leading to antibiotic resistance [ 32 , 33 ]. Biofilm formation on the surfaces of medical devices is therefore a key feature of disease progression, and so the antiadhesion and antibacterial functionalization of PVC-ETTs with hydrophilic polymers and stable broad-spectrum antibacterial agents is particularly important in the prevention of biofilm formation and bacterial infection [ 34 37 ]. It is therefore also critical to suppress bacterial adhesion and multiplication during the initial stage.…”
Section: Resultsmentioning
confidence: 99%
“…exigua, P. sorghina, P. macrostoma, P. glomerata, P. macdonaldii, P. tracheiphila, P. multirostrata, P. proboscis, and P. foveata , etc. (Rai et al 2009a , b , c , 2021a , b ). As shown in Fig.…”
Section: Secondary Metabolites Are Responsible For Antimicrobial Acti...mentioning
confidence: 99%
“…An open gap of 0.9 mm was created by a "wound", as reported in the Section 4. The reaction of the cells to fill the damaged area was inspected microscopically over time (6,12, and 18 h) (Figure 2). In the control sample, the open gap remained unchanged after 6 h (0.9 mm), with a reduction of 25% and 60% after 12 h and 18 h, respectively.…”
Section: Effect Of Vitamin D3 and Silver Nanoparticles On Wound Heali...mentioning
confidence: 99%
“…It has been demonstrated that silver nanoparticles (AgNPs) are useful for different medical applications as medical products, medical instruments, water filtration, personal hygiene products, and others [11]. AgNPs are well known for their unique physical, chemical, and biological properties, which depend on their size, shape, and surface charge [12]. Thanks to their size (1-100 nm), the particles enter cells mostly through endocytosis and release of ions into the cytoplasm [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation